First-line treatment of chronic myeloid leukemia with nilotinib: critical evaluation - Piccaluga, Pier Paolo (Dove Medical Press, 2012)
The therapeutic landscape of chronic myeloid leukemia (CML) has changed dramatically in the last decade. In particular, the availability of imatinib mesylate, a tyrosine kinase inhibitor targeting BCR-ABL, has led to profound and durable remissions in the majority of patients. However, a couple of issues have emerged and partially obscured this scenario. First, it has become clear that a significant proportion of patients either present with primary resistance to imatinib or develop secondary resistance sooner or later during treatment. Second, although the drug is generally well tolerated, a percentage of patients eventually cease treatment because of toxicity. Bearing this in mind, second-generation tyrosine kinase inhibitors have been introduced, including nilotinib. Phase I and II studies indicate remarkable activity for this compound in CML cases resistant to imatinib, including some of those carrying BCR-ABL1 mutants. More recently, two Phase II studies and a III randomized Phase clinical trial demonstrated the superiority of nilotinib compared with imatinib in terms of complete cytogenetic and major molecular responses, which are two relevant surrogate measures of long-term survival in CML. In this paper, we review the most relevant data on nilotinib as first-line treatment for CML, and discuss the rationale for its routine use, as well as some possible future perspectives for CML patients.